Design and analysis of experiments Vol 2 : advanced experimental design - Klaus, Hinkelmann; Kempthorne, Oscar (New Delhi Wiley, 2014)
General incomplete block design; Balanced incomplete block designs; Construction of balanced incomplete block designs; Partially balanced incomplete block designs; Construction of partially balanced incomplete block desigjns;More block designs and blocking structures; Two-level factorial designs; Confounding in 2n factorial designs; Partial confounding in 2n factorial designs; Designs with factors at three levels; General symmetrical factorial Design; Confounding in asymmetrical factorial designs; Fractional factorial disincline effect plans'; Supersaturated desgind;search designs; robust-design experiments; lattice designs; crossover designs.
Keywords: Statistical Mathematics